(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Banks in India consider NPAs to be a leading problem, as they disrupt the country’ s economy and financial stability. Reforms, recapitalization, the foundation of the Insolvency and Bankruptcy Board of India